Enhanced inhibitory neurotransmission in the cerebellar cortex of Atp1a3‐deficient heterozygous mice. (4th June 2013) - Ikeda, Keiko; Satake, Shin'Ichiro; Onaka, Tatsushi; Sugimoto, Hiroki; Takeda, Naoki; Imoto, Keiji; Kawakami, Kiyoshi
Key points Mutations of ATP1A3 cause rapid‐onset dystonia with parkinsonism (RDP) and alternating hemiplegia of childhood (AHC). The mRNA of Atp1a3 was highly expressed in molecular‐layer interneurons and Purkinje cells in the developing mouse cerebellar cortex, and the gene product was observed as dots in the molecular layer, on the surface of Purkinje cell soma and the pinceaux. Here we report that Atp1a3+/− mice showed increased symptoms of dystonia when being administrated kainate into cerebellum. We also found enhanced inhibitory neurotransmission between molecular‐layer interneurons and Purkinje cells in the developing cerebellum of Atp1a3+/− mice. These findings suggest that ATP1A3 haploinsufficiency in the cerebellum has some effect on the inhibitory, but not the excitatory, circuitry and the interaction among different cell types during development. Disturbances of the cerebellar inhibitory network seem to be the underlying pathophysiological mechanism of dystonia among the increasing spectrum of complex neurological symptoms in RDP and AHC. Abstract Dystonia is characterized by excessive involuntary and prolonged simultaneous contractions of both agonist and antagonist muscles. Although the basal ganglia have long been proposed as the primary region, recent studies indicated that the cerebellum also plays a key role in the expression of dystonia. One hereditary form of dystonia, rapid‐onset dystonia with parkinsonism (RDP), is caused by loss of function mutations of the gene for the Na pump α3 subunit (ATP1A3). Little information is available on the affected brain regions and mechanism for dystonia by the mutations in RDP. The Na pump is composed of α and β subunits and maintains ionic gradients of Na+ and K+ across the cell membrane. The gradients are utilized for neurotransmitter reuptake and their alteration modulates neural excitability. To provide insight into the molecular aetiology of RDP, we generated and analysed knockout heterozygous mice (Atp1a3+/−). Atp1a3+/− showed increased symptoms of dystonia that is induced by kainate injection into the cerebellar vermis. Atp1a3 mRNA was highly expressed in Purkinje cells and molecular‐layer interneurons, and its product was concentrated at Purkinje cell soma, the site of abundant vesicular γ‐aminobutyric acid transporter (VGAT) signal, suggesting the presynaptic localization of the α3 subunit in the inhibitory synapse. Electrophysiological studies showed that the inhibitory neurotransmission at molecular‐layer interneuron–Purkinje cell synapses was enhanced in Atp1a3+/− cerebellar cortex, and that the enhancement originated via a presynaptic mechanism. Our results shed light on the role of Atp1a3 in the inhibitory synapse, and potential involvement of inhibitory synaptic dysfunction for the pathophysiology of dystonia.